Discovery of Ethyl 2-Nitro-3-Arylacrylates Molecules as T3SS Inhibitor Reducing the Virulence of Plant Pathogenic Bacteria Xanthomonas - Jiang, Shan; Li, Hui; Ahmed, Wasim; Xiang, Xuwen; Song, Gaopeng; Cui, Zi-Ning (Frontiers in Microbiology, 2019)
Xanthomonas oryzae pv. oryzae (Xoo) is a gram-negative pathogen which causes leaf blight disease. Known traditional bactericides are not much more effective in inhibiting this bacteria than before. Selecting the virulence factor of the bacteria as the target without affecting their growth has been considered as a novel method for developing new anti-microbial drugs. Type III secretion systems (T3SS) are one of the important and highly conserved virulence factors in most gram-negative pathogens, which has been considered as an effective target to develop new anti-microbial drugs. In order to discover potential anti-microbial drugs against Xoo pathogens, a series of ethyl 2-nitro-3-arylacrylates compounds were screened. Among them, the compounds I-9, I-12, and I-13 could highly inhibit the promoter activity of a harpin gene hpa1, which were used to further check for the influence on bacterial growth and on the hypersensitive response (HR) caused by Xoo bacteria on non-host plants. The results showed that above compounds could reduce HR without affecting bacterial growth and survival. Moreover, qRT-PCR analysis indicated that treatment with the three inhibitors (I-9, I-12, and I-13) could suppress the expression of the Xoo T3SS in different extent. The mRNA levels of representative genes in the hrp cluster, including the key regulatory genes hrpG and hrpX, were decreased. Last but not least, in vivo test ensured that the above compounds reduced the disease symptoms of Xoo on the rice and Xcc on the Chinese radish.